2018
DOI: 10.2147/idr.s174506
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and genotypic characterizations of extended-spectrum beta-lactamase-producing <em>Escherichia coli</em> in Thailand

Abstract: PurposeExtended-spectrum β-lactamases (ESBLs) have become an issue in community worldwide due to an increase in antibiotic resistance over the past decade. This study was aimed to investigate the phenotypic and genotypic characteristics of ESBL-producing Escherichia coli in Thailand.Materials and methodsIn this study, all clinical isolates collected from tertiary hospitals in Thailand were identified as E. coli by biochemical tests and MALDI-TOF mass spectrometry. ESBL-producing E. coli was preliminary screene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 21 publications
5
30
0
Order By: Relevance
“…Both groups of human and swine isolates had no significant differences in the distribution of these bla genes. Similar to our findings, previous studies showed that the bla CTX-M family had the highest prevalence among those typical E. coli ESBL encoding genes, followed by bla TEM and bla SHV either from clinical, animal, or environmental isolates 2325. The prevalence of bla CTX-M-15 has risen over time worldwide and is dominant in most countries.…”
Section: Discussionsupporting
confidence: 90%
“…Both groups of human and swine isolates had no significant differences in the distribution of these bla genes. Similar to our findings, previous studies showed that the bla CTX-M family had the highest prevalence among those typical E. coli ESBL encoding genes, followed by bla TEM and bla SHV either from clinical, animal, or environmental isolates 2325. The prevalence of bla CTX-M-15 has risen over time worldwide and is dominant in most countries.…”
Section: Discussionsupporting
confidence: 90%
“…The frequencies of the genes aac(3)II, tetA, and dfrA1 in the evaluated E. coli strains were higher than those in uropathogenic strains of E. coli in Iran, whereas the frequencies of the genes qnrA and sul1 were similar to those in these strains [15]. In contrast, the frequency of the gene TEM, was similar to that in E. coli strains identified in other parts of the world [30,31]. The bacterial horizontal transfer of antimicrobial resistance genes by means of plasmids, transposons, and integrons favours the dissemination of multiresistant strains [32].…”
Section: Discussionmentioning
confidence: 50%
“…Suspected colonies of the Enterobacteriaceae E. coli (pink to purple) and K. pneumoniae (bluish green) were picked from each selective plate and streaked onto nutrient agar (Oxoid) at 37 °C for 24 h, followed by biochemical identification using Vitek2 (bioMérieux, Marcy 1′ Etoile, France). All the E. coli and K. pneumoniae isolates were then identified and confirmed by matrix-assisted laser desorption ionization/time-of-flight mass spectrometry (MADLI-TOF MS) ( Bubpamala et al, 2018 ). All the confirmed isolates were stored at 2 °C–8 °C until antimicrobial drug susceptibility testing and evaluation of ESBL production.…”
Section: Methodsmentioning
confidence: 99%